INTERNALIZATION OF THE READING HABIT CHARACTER THROUGH THE DOLAN LITERACY PROGRAM FOR ELEMENTARY SCHOOL-AGED CHILDREN - Hesti Awandani Pangestu; Aldo Redho Syam; Lilis Sumaryanti (Al-Mudarris: Journal Of Education, 2025)
This study examines the internalization of the character of reading enjoyment through the Dolan Literacy Program for elementary school-aged children at the Community Reading Center (Taman Bacaan Masyarakat) in Tunggur Village, Slogohimo Subdistrict, Wonogiri Regency. The program is designed as a form of literacy education based on enjoyable, contextual, and inclusive activities, integrated with a character-building approach. This research employs a qualitative descriptive method. Data collection techniques include interviews, observation, and documentation. The data were analyzed using descriptive analysis. The findings show that the internalization of the reading habit character is carried out through three main approaches: conditioning (positive habituation), providing understanding (value-based comprehension), and uswatun hasanah (role modeling). Activities such as open reading corners, group reading outings, storytelling competitions, and book exploration picnics have effectively increased children's engagement in reading activities. In addition, the development of indicators of the reading enjoyment character in elementary-aged children can be observed through increased curiosity, independence, reading consistency, and the ability to retell the content of what they have read. This program is also in line with Minister of Education and Culture Regulation Number 64 of 2013, which emphasizes the importance of fostering a love for reading as part of character education in primary education. Overall, the Dolan Literacy Program has successfully created a collaborative and enjoyable literacy ecosystem that not only enhances children's reading interest but also strengthens character values in a sustainable manner.